The Meaning of the Pantang Larang on 1 Muharram for the Pemangkat Malay Society - Ramadhan, Iwan; Khosihan, Aan; Nurazizah, Silmi; Suriyanisa (NALAR, 2024)
This study aims to explore the meaning of Pantang Larang on 1 Muharram for the Malay society in Pemangkat, Sambas Regency. This article is a qualitative study with a phenomenological approach. Data collection was conducted in July 2023 through participant observation and in-depth interviews. The data were analyzed according to Milles and Huberman's qualitative analysis model: data reduction, data display, and conclusions. The data obtained shows that there are five restrictions on the date of 1 Muharram for the Malay people in Pemangkat: the restriction of doing strenuous work, the restriction of traveling, the restriction to conducting a wedding celebration, the restriction of going to the forest and the plantation, and the restriction of playing outside for children. Data analysis found that the Malay society in Pemangkat meant Pantang Larang on 1 Muharram as an effort to achieve self-control, safety, health, and individual welfare. This meaning is formed based on ancestral experience stories from generation to generation in the Malay society in Pemangkat, creating cultural continuity.